PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN IKLIM ORGANISASI TERHADAP PRODUKTIVITAS KARYAWAN - Wahyudi, Didi; Khaeruman, Khaeruman; Susanto, Budi (Yayasan Education and Social Center, 2024)
The aim of this research is to determine the influence of transformational leadership and organizational climate on employee productivity. This research method is a correlational quantitative approach. Namely to test the influence of the independent variable on the dependent variable which in this study uses 2 independent variables (Transformational Leadership, Organizational Climate) and 1 dependent variable (Productivity). The approach used in this research is a survey method of 80 employees. The results of this research are that there is a significant influence of transformational leadership on employee productivity. Based on the SPSS Version 26 calculation results, the value of tcount > ttable (6,618 > 1.664488), then H0 is rejected and H1 is accepted. And there is a significant influence of organizational climate on employee productivity. Based on the SPSS Version 26 calculation results, the value tcount > ttable (2,262 > 1.664488), then H0 is rejected and H2 is accepted. Based on the significance test, it was found that there is a significant influence between transformational leadership and organizational climate on production employee productivity